2019
DOI: 10.1021/acs.jmedchem.8b01936
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Histone Deacetylase 10: Hydrogen Bonding to the Gatekeeper Residue is Implicated

Abstract: The discovery of isozyme-selective histone deacetylase (HDAC) inhibitors is critical for understanding the biological functions of individual HDACs and for validating HDACs as drug targets. The isozyme HDAC10 contributes to chemotherapy resistance and has recently been described to be a polyamine deacetylase, but no studies toward selective HDAC10 inhibitors have been published. Using two complementary assays, we found Tubastatin A, an HDAC6 inhibitor, to potently bind HDAC10. We synthesized Tubastatin A deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 58 publications
(170 reference statements)
9
88
1
1
Order By: Relevance
“…It has an IC 50 value of 15 nM on HDAC6 and is more than 50‐fold selective over HDAC8, more than 1000‐fold selective over HDAC1 and more than 2000‐fold selective over HDAC2‐5, HDAC7 and HDAC9 making it one of the most selective HDAC6 inhibitors. In a more recent study, tubastatin A was found to be an equally potent binder of HDAC10, which was also confirmed in a cellular assay [83] . Surprisingly, the crystal structures of tubastatin A with zebrafish HDAC6 (PDB ID: 6THV) and with “humanized” zebrafish HDAC10 having A24E and D94A mutations (PDB ID: 6WBQ) showed a substantially different binding mode of this inhibitor [84] .…”
Section: Strategies To Design Selective Hdac Inhibitorsmentioning
confidence: 86%
See 1 more Smart Citation
“…It has an IC 50 value of 15 nM on HDAC6 and is more than 50‐fold selective over HDAC8, more than 1000‐fold selective over HDAC1 and more than 2000‐fold selective over HDAC2‐5, HDAC7 and HDAC9 making it one of the most selective HDAC6 inhibitors. In a more recent study, tubastatin A was found to be an equally potent binder of HDAC10, which was also confirmed in a cellular assay [83] . Surprisingly, the crystal structures of tubastatin A with zebrafish HDAC6 (PDB ID: 6THV) and with “humanized” zebrafish HDAC10 having A24E and D94A mutations (PDB ID: 6WBQ) showed a substantially different binding mode of this inhibitor [84] .…”
Section: Strategies To Design Selective Hdac Inhibitorsmentioning
confidence: 86%
“…Geraldy et al. prepared a series of tubastatin A analogs with various cap group modifications and found that increasing the flexibility of the positively charged nitrogen atom by opening the tetrahydropyridine ring sometimes yields highly active and selective HDAC10 inhibitors [83] . A simple tubastatin A analog with dimethylaminomethyl substituent on the indole ring (compound 55 , Figure 4) shows an IC 50 of 5 nM on HDAC10, is 40‐fold selective over HDAC6, 80‐fold selective over HDAC8 and more than 100‐fold selective over HDAC1‐3.…”
Section: Strategies To Design Selective Hdac Inhibitorsmentioning
confidence: 99%
“…However, due to some severe adverse effects of multitarget HDACIs [ 149 ], Géraldy et al [ 150 ] investigated HDAC10-specific inhibitors and found that tubastatin A tightly bound to HDAC10 in HeLa cells with its basic amine in the cap group. Based on an HDAC10 homology model, they revealed that a hydrogen bond falls in between a cap group nitrogen, and a gatekeeper residue Glu 272 contributes to the tight binding.…”
Section: Hdac10 Inhibitorsmentioning
confidence: 99%
“…In addition, they examined the inhibitory properties of HDAC10 under different drug concentrations (5 and 50 μM), which indicates both azumamides C and azumamides E markedly inhibit HDAC10. The HDACIs tubastatin A and PCI-34051 have the same N-benzylindole core [ 150 , 152 ]. After hybridizing these two inhibitors, Morgen et al [ 153 ] synthesized dihydroxamic acids, which significantly suppressed the viability of neuroblastoma cells and played the role of potent inhibitor of HDAC10.…”
Section: Hdac10 Inhibitorsmentioning
confidence: 99%
“…The discovered difference clearly indicates that the mechanisms of the antiviral action of these compounds substantially differ. It has recently been shown that the tubastatin A scaffold ensures simultaneous binding to HDAC6 and HDAC10 [ 67 ]. The affinity of tubastatin A binding to the active site of HDAC10 is ensured by the interaction of the tertiary amino group of the inhibitor’s cap with the carboxyl group of the Glu272 residue of the enzyme.…”
Section: Discussionmentioning
confidence: 99%